2018
DOI: 10.1007/s10554-018-1446-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum uric acid levels with SYNTAX score II and long term mortality in the patients with stable angina pectoris who undergo percutaneous coronary interventions due to multivessel and/or unprotected left main disease

Abstract: Serum uric acid (SUA) level was shown in various studies to be related to the presence of coronary artery disease and subsequent cardiovascular events. The aim of the present study was to evaluate the association of SUA with SYNTAX score II (SSII) and the long-term prognosis of patients with stable angina pectoris who underwent percutaneous revascularization due to multivessel disease (MVD) and/or unprotected left main disease (UPLMD). Two-hundred and ninety patients with MVD and/or UPLMD who were treated cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
3
9
0
Order By: Relevance
“…The most important issue in these subjects is the possible relationship between UA levels and the extent and severity of Coronary Artery Disease (CAD). As was also shown in Table 2 , most of the publications on this topic show that UA correlates with CAD, as defined as both the number of vessels involved [ 48 ] and specific scores, such as Gensan [ 49 ] or Syntax [ 50 ]. However, other studies did not identify this association [ 9 , 51 , 52 ].…”
Section: Uric Acid and Chronic Coronary Syndromementioning
confidence: 99%
“…The most important issue in these subjects is the possible relationship between UA levels and the extent and severity of Coronary Artery Disease (CAD). As was also shown in Table 2 , most of the publications on this topic show that UA correlates with CAD, as defined as both the number of vessels involved [ 48 ] and specific scores, such as Gensan [ 49 ] or Syntax [ 50 ]. However, other studies did not identify this association [ 9 , 51 , 52 ].…”
Section: Uric Acid and Chronic Coronary Syndromementioning
confidence: 99%
“… (Gaubert et al, 2018) 37 Endothelial dysfunction with reactive hyperemia (RH) and severity of atherosclerosis Non-invasive peripheral arterial tonometry (PAT) and angiography The uric acid level had a significant relationship with Reactive Hyperemia Index/RHI (β= -0.17, p<0.001), and the uric acid level was associated with the Gensini score and SYNTAX score (p<0.001) (Joo et al, 2018) 27 Major adverse event (MAE): the cause of all mortality, non-fatal myocardial infarction, and revascularization. Angiography Uric acid was not an independent predictor of MAE (HR 1.110; 95% CI 0.980-1.257; p= 0.100) (Karabağ et al, 2019) 39 SYNTAX score II (SII) and long-term mortality Angiography Uric acid and SYNTAX independent predictors of long-term mortality (HR 1.24, 95% CI 1.046-1.482, p= 0.014; HR 1.042, 95% CI 1.007-1.079, p= 0.018) …”
Section: Resultsmentioning
confidence: 99%
“…In a study involving 64 aortic stenosis patients, Demir B et al found a significant relationship between CAVD and elevated uric acid level, which they accepted as an indirect indicator of increased oxidative stress and endothelial dysfunction [21]. In addition to this, uric acid was shown to promote development of atherosclerosis via inducing inflammation and also associated with the disease severity and prognosis in atherosclerotic patients [22,23]. All these data and our current findings suggest that uric acid may have a role in the development of aortic sclerosis and CAVD.…”
Section: Discussionmentioning
confidence: 99%